Medicometric Portrait of Dr. Subhas Mukherjee, Late Recognized Pioneer of Historic Creation of India’s First and World’s Second IVF Baby - Koley, Susanta (Journal of Data Science, Informetrics, and Citation Studies)
Dr. Subhas Mukherjee (Mukhopadhyay), Bengalee Physician cum Medical Scientist, is a pioneer of IVF in India, a late recognized pioneer of Asia’s as well as India’s first and world’s second test tube baby. This bibliometric study draws a painful story of late recognition and of defeat in the competition for the Nobel prize. It also analyses on his biographical facts and his 99-publications published during the period of 1957-1981 with 124 co-authors. He has 22 single authored and 73 multi-authored papers. His highest publication is 10.5 (54.55%) per year during 1972-76 when his age range was 42-46 years and second highest productivity is 21(21.21%) papers per year during 1967-71 when his age was between 37-41 years. He generated the highest papers 16 in collaboration with his closet collaborator D L Podder, during the period 1972-76. He mostly preferred Proc. Ind. Sc. Cong. (25 papers) for his publications. The most frequently used key terms Human (19) times followed by Human Chorionic Gonadotrophin (HCG) (12), Rats (10), Infertility (8), Pregnancy (7). Finally, it shows that data set does not follow Bradford distribution.
Keywords: Scientometric; Medicometric; Subhas Mukherjee (Mukhopadhyay); Human test tube baby; IVF; Asia’s first IVF baby; Reproductive physiology; Kolkata.